Abundance analysis of the γ Doradus–δ Scuti hybrid metallic line (Am) star HD 8801. Issue 7 (1st August 2013) - Neuteufel, R.; Weiss, W.; Handler, G.
Abstract Low frequency oscillation, typical for γ Doradus g‐mode type stellar core sensitive pulsation, as well as higher frequency δ Scuti type pulsation typical for p ‐modes, sensitive to the envelope, make HD 8801 a remarkable hybrid pulsator with the potential to probe a stellar structure over a wide range of radius. In addition HD 8801 is a rare pulsating metallic line (Am) star. We determined the astro‐physical fundamental parameters to locate HD 8801 in the H‐R diagram. We analyzed the element abundances, paying close attention to the errors involved, and confirm the nature of HD 8801 as a metallic line (Am) star. We also determined an upper limit on the magnetic field strength. Our abundance analysis is based on classical techniques, but uses for the final step a model atmosphere calculated with the abundances determined by us. We also discuss spectropolarimetric observations obtained for HD 8801. This object is remarkable in several respects. It is a nonmagnetic metallic line (Am) star, pulsating simultaneously in p‐ and g‐modes, but also shows oscillations with periods in between these two domains, whose excitation requires explanation. Overall, the pulsational incidence in unevolved classical Am stars is believed to be quite low; HD 8801 does not conform to this picture. Finally, about 75 % of Am stars are located in short‐period binaries, but there is no evidence that HD 8801 has a companion. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)